A Journey To (Enjoy) Coffee: A Marketing Strategy Of Coffee On The Bus Yogyakarta During Covid19 Pandemic - Suseno Hendratmoko; Endah Kurniawati; Heru Sutapa (Program Pascasarjana STIE Amkop Makassar, 2022)
The selection of a marketing strategy is one of the important things that must be done by a business agent to maintain the sustainability of a business in a fierce business competition environment. The Covid-19 pandemic, which has lasted from 2020 until now, had a significant impact on the sustainability of business type. Coffee on the bus Yogya, one of the business agents that get the impact of the covid-19 pandemic, endemic is trying to survive and maintain the business. Coffee on the bus offers a new concept of enjoying coffee while enjoying the view of the city of Yogyakarta through a predetermined time and several routes. This marketing strategy was chosen as one of the business strategies to keep running the business activities. The design of this research is descriptive qualitative. The purpose of descriptive qualitative research is to know, describe, and reveal the conditions related to the marketing strategy that has been done by the company. The data collection method used is an interview, observation, and documents related to the research. Data analysis was carried out through several stages, they are reduction, display, and verification/drawing conclusion. The results show that Coffee on the bus Yogyakarta in running its business uses marketing strategies related to the marketing mix, namely product, price, place, promotion, people, physical evidence, and process. Keywords: Marketing strategy, Coffee on The Bus Yogyakarta, Covid19